(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The Tanah Laut area in South Kalimantan Province is a rapidly developing area, in line with the plan to relocate the country’s capital. Therefore, the need for groundwater as a water resource in community life in that area needs to be supported by various studies. This research is intended as a hydrogeological survey in Tanah Laut District, to determine the local groundwater hydrochemistry and its potential for sea water intrusion. The research was conducted in the field by collecting data on the physical properties of groundwater in 155 dug wells and 50 artesian wells. Several groundwater samples representing free and confined aquifers were tested for physical/chemical properties in the laboratory. The analysis was performed based on groundwater table, pH, electrical conductivity (EC) and groundwater facies. The results showed that free groundwater has a pH of 6.1 - 8.4 and a total dissolved solid (TDS) ranged from 20.3 - 964 μS/cm, while the confined groundwater had a pH of 4.01 - 9.95 and a TDS of 28 – 2,670 μS/cm. Groundwater facies vary widely, generally dominated by Na and bicarbonate ions. Brackish groundwater was found in confined aquifers in two locations, namely Asam Jaya and Mekar Sari, indicating that the research area has the potential of sea water intrusion.